Assessment of the cognitive visualization process used in learning geometry - Beauset, Romain; Lequeu, Clarisse; Duroisin, Natacha (Mesure et évaluation en éducation)

(untitled) (ADMEE-Canada, 2024)
Assessment of cognitive processes involved in the learning of geometry is a real challenge to understand difficulties learners faced. This article investigates the assessment of cognitive processes through two studies on the spatial visualization ability, a first in plane geometry and a second in 3D geometry. The first study uses a paper-and-pencil test used to assess the ability to visualize plane figures at the end of primary education. The second employs a test that uses virtual material, as an alternative to paper-and-pencil test, to assess 3D spatial visualization with primary and secondary learners. After a description of the two assessment tools, the aim of this article is to take a critical look at the evaluation of cognitive processes by presenting the limits relating to these tools and by identifying the alternatives offered notably with the emergence of new technologies.